Effect of different mechanical damage degrees in sorghum seeds - Netto, Dea Alecia Martins; Borba, Cleverson Silveira; Oliveira, Antônio Carlos de; Azevedo, João Tito de; Andrade, Ramiro Vilela (Pesquisa Agropecuaria Brasileira, 1999)
Twelve seed lots of sorghum (Sorghum bicolor L. Moench.), cultivar BR 303, with different degrees of mechanical damage were evaluated on germination and vigor test. The data of mechanical damage based upon fast green test, accelerating aging, cold test, speed of emergence and stand establishment. The experiment was conducted in Seed Laboratory Analysis of the Embrapa-Centro Nacional de Pesquisa de Milho e Sorgo (CNPMS), in Sete Lagoas, MG, Brazil. There were significantly decrease through regressions analysis on germination and vigor tests, when the seeds were damaged up to 5%; from 5% to 15% of damage the decrease was not significant. From 15% to 23% of damage, the germination and vigor declined 22.5% compared to the control. The immediate hazard effect of mechanical damages on physiological quality of sorghum seeds could be detected by several tests.